Dissemination of local sub-variants of SARS-CoV-2 detected by detailed mutation analysis in wastewater-based epidemiology - Ryo Honda; Takashi Abe; Tomoya Baba; Yui Araki; Tomohiro Kuroita; Ryo Iwamoto; Mayo Ito; Nami Okamura; Marie Kenza Yousri; Takashi Tamura; Satoshi Ezaki; Masanori Arita (PLoS ONE, 2025)
Wastewater-based epidemiology (WBE) is effective for identifying the predominant SARS-CoV-2 variants within specific populations as well as early warning of disease outbreaks. The variant analysis in WBE has been limited to quantifying the proportion of variants, and it has been unable to trace their origins and dissemination pathways. This study aims to elucidate the emergence and transmission of locally predominant SARS-CoV-2 sub-variants through detailed mutation analysis in wastewater genomic surveillance. Genome mutations at each nucleotide position in the S region were examined to identify locally unique sub-variants in geographically distinct cities of Komatsu and Hamamatsu. Notably, the XBT variant, which had never been reported in clinical samples from Japan, was detected in wastewater in Komatsu. Moreover, a unique sub-variant of BA.5 was detected in Komatsu for a duration of 17 weeks whereas it was absent in Hamamatsu. Mutation analysis also revealed significant differences in the duration of the common BA.2.75 sub-variant’s prevalence in Komatsu for 35 weeks, in contrast to only one week in Hamamatsu. These findings underscore the efficacy of wastewater-based genomic epidemiology in identifying the timing of variant entry and prevalence duration, enhancing our understanding of the origins, transmission pathways, and evolutionary trajectories of epidemically important variants.